Disaster Management and Relief Operations in Volatile Environments: A Survey of the Niger Delta Region - Faghawari D. Nyanayon; Edih O. University (Britain International for Academic Research (BIAR-Publisher), 2022)
Disasters have been described as sudden and unpleasant experience which are rather inevitable to man's existence. Hence, the need to understand the dynamics of disaster management and relief operations is timely considering the massive destruction of lives, properties and infrastructures occasioned by covid'19 pandemic as well as the 2022 flood disaster. This study therefore, examines disaster management and relief operations in volatile environments , the Niger Delta region perspective and the objectives are, to understand the dynamics of disaster management and relief operations, to understand the skills or techniques in managing disasters and relief operations and to create public awareness on the essence of knowing the basic tips of mitigation, preparedness, response, and recovery on disaster management. The paper is considered sequentially as follows; introduction, concept of disaster management, components of disaster management, relief operations techniques and conclusion. This research work will further enhance public sensitization and understanding the dynamics of disaster management. It will serve as a guide to governments and other stakeholders in formulating policies and programmes on disaster management and relief operations in Nigeria.